2022
DOI: 10.3390/ijms231810212
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cockayne Syndrome Group B Protein in Replication Stress: Implications for Cancer Therapy

Abstract: A variety of endogenous and exogenous insults are capable of impeding replication fork progression, leading to replication stress. Several SNF2 fork remodelers have been shown to play critical roles in resolving this replication stress, utilizing different pathways dependent upon the nature of the DNA lesion, location on the DNA, and the stage of the cell cycle, to complete DNA replication in a manner preserving genetic integrity. Under certain conditions, however, the attempted repair may lead to additional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 147 publications
2
10
0
Order By: Relevance
“…The toxic combination of CSB and BRCA2 is a feature that has also been previously observed in BRCA2-depleted CSB-KO cells upon exposure to HU, olaparib, and cisplatin [18]. The work presented here lends further support to the previously claimed notion [12,43] that CSB is both a promising biomarker and a potential target in cancer treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The toxic combination of CSB and BRCA2 is a feature that has also been previously observed in BRCA2-depleted CSB-KO cells upon exposure to HU, olaparib, and cisplatin [18]. The work presented here lends further support to the previously claimed notion [12,43] that CSB is both a promising biomarker and a potential target in cancer treatment.…”
Section: Discussionsupporting
confidence: 87%
“…Fork reversal is thought to protect the stability of stalled forks, allowing resumption of DNA synthesis without chromosome breakage [10,11]. Many proteins have been implicated in fork reversal [12,13], including the recombinase RAD51 [14], PARP1 [7,8],…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that loss of CSB restores chemosensitivity in cells depleted with both SMARCAL1 and BRCA2, which is likely due to a defect in CSB-mediated BIR repair of stalled forks ( 17 ). Our finding adds further evidence to growing lines of studies ( 35 , 77 ) suggesting that CSB is a promising target in targeted cancer therapy.…”
Section: Discussionsupporting
confidence: 82%
“…Like SMARCAL1, CSB (Cockayne syndrome group B) is a DNA translocase that belongs to the SNF2 helicase family ( 12 ). First reported for its role in transcription-coupled nucleotide excision repair (TC-NER) ( 28 , 29 ), CSB has been implicated in DNA DSB repair ( 30–34 ) and the replication stress response ( 17 , 35 , 36 ). CSB possesses an intrinsic fork reversal activity in vitro ( 17 ), which is likely to be highly regulated in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…CSB protein acts as SNF family chromatin remodeler with ATPase activity that together with CSA protein is best known for the role in transcription-coupled nucleotide-excision DNA repair (TC-NER). These proteins also have a role in repair of DSB, and a variety of other functions as well ( Jaarsma et al, 2013 ; Vessoni et al, 2020 ; Walker and Zhu, 2022 ). Mechanistically, during TC-NER, CSB recognizes nuclear but also mitochondrial DNA lesions ( Scheibye-Knudsen et al, 2012 ; Scheibye-Knudsen et al, 2013 ) that cause RNA stalling in the active transcribed regions, and in turn promotes either backtracking of stalled RNA polymerase or its removal via ubiquitination.…”
Section: Introductionmentioning
confidence: 99%